Peran Kepuasan Kerja dalam Memediasi Pengaruh antara Employee Engagement terhadap Kinerja Pegawai di Lingkungan Pemerintah Distrik Jayapura Utara - Almalika Firgandhini Kadri; H. Muhdi B. Hi Ibrahim; Andri Irwanan; Septyana Prasetianingrum (Universitas Yapis Papua, 2023)
This study aims to determine the role of job satisfaction in mediating the effect of employee engagement on employee performance in the Jayapura Utara district government. Samples were taken using saturated sampling method with a total sample of 113 respondents. The analytical method used is mediation. The results of the study show hat employee engagement has no effect on employee performance in the Jayapura Utara district government. Employee engagement has a positive effect on employee job satisfaction in the Jayapura Utara district government. Job satisfaction has a positive effect on employee performance in the Jayapura Utara district government. Job satisfaction can mediate the effect of employee engagement on employee performance in the Jayapura Utara district government